Defining and Adhering to Standards of Professionalism in Residency - Jeffrey Berger; Amanda Hopkins; Gurwinder Gill (Association of American Medical Colleges, 2015)
Abstract This resource is a learning module developed for first-year residents to gain exposure to the tenets of professionalism, both in the general practice of medicine and within their own specialty. By completion of this module, each resident will have articulated his or her personal standards of professional behavior and have made a written commitment to strive for those standards in everyday clinical situations. Through the use of general case-based scenarios, learners may both identify unprofessional behavior and discuss real-world strategies for correcting it. However, it is important to note that standards of professionalism may be slightly different based on institutional or state policies, and therefore, individual policies should be reviewed prior to this exercise. The clinical cases included in this module were chosen because they address specific issues of professionalism a resident is likely to encounter during his or her training. These scenarios are based on personal experience and anonymous input from residents in training. To evaluate the effectiveness of this module, a brief survey was distributed to current and former residents who had completed the module. The survey presented a series of 10 statements and asked participants to report their level of agreement with each statement on a 5-point Likert scale. Thirteen of the 40 participants responded: four 2013 graduates, two 2014 graduates, one CA-3 resident, two CA-2 residents, and four CA-1 residents.